2003
DOI: 10.1021/bi034189d
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferase Activity Can Be Modulated by Small Conformational Changes of Acceptor Substrates

Abstract: A range of N-acetyllactosamine derivatives (compounds 4-7) that have restricted mobilities around their glycosidic linkages have been employed to determine how small changes in conformational properties of an oligosaccharide acceptor affect catalytic efficiencies of glycosylations by alpha-2,6- and alpha-2,3-sialyltransferases and alpha-1,3-fucosyltransferases IV and VI. Restriction of conformational mobility was achieved by introducing tethers of different length and chemical composition between the C-6 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Plasticity of the active site and the flexibility between acceptor-and donor-binding sites may help to explain how enzymes with the same overall structure are used for the formation of more than one type of glycosidic linkage and for the transfer of more than one monosaccharide. It has been shown that constraining glycosyl acceptors into a variety of conformations can have a significant impact on the kinetic parameters of the glycosyltransferases that recognize them (62). Much more work is needed to begin to understand how Alg2 can carry out an R1,3-mannosylation when the trisaccharide intermediate is bound, while binding of the tetrasaccharide induces an R1,6-mannosylation, thus changing the linkage specificity by changing the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity of the active site and the flexibility between acceptor-and donor-binding sites may help to explain how enzymes with the same overall structure are used for the formation of more than one type of glycosidic linkage and for the transfer of more than one monosaccharide. It has been shown that constraining glycosyl acceptors into a variety of conformations can have a significant impact on the kinetic parameters of the glycosyltransferases that recognize them (62). Much more work is needed to begin to understand how Alg2 can carry out an R1,3-mannosylation when the trisaccharide intermediate is bound, while binding of the tetrasaccharide induces an R1,6-mannosylation, thus changing the linkage specificity by changing the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable effort has also been dedicated to the design and synthesis of inhibitors of sialylation processing enzymes focusing on the receptor specificity by using modified lactose and lactosamine [37][38][39]. Through the studies of structure-effective relationship, Wlasichuk and co-workers reported that the C-6′ hydroxyl and acetamido group of LacNAc are essential for sialylation by rat liver α2,6-sialyltransferase [37].…”
Section: Oligosaccharide Derivativesmentioning
confidence: 99%
“…Through the studies of structure-effective relationship, Wlasichuk and co-workers reported that the C-6′ hydroxyl and acetamido group of LacNAc are essential for sialylation by rat liver α2,6-sialyltransferase [37]. Methylation of the C-6 and C-2′ hydroxyls of LacNAc had only a minimal effect on α2,3-sialyltransferase [39], but there was no inhibition of α2,3-sialyltransferase when the C-2′ hydroxyl of LacNAc was epimerized [38]. In addition, fluorine-containing mucin core 2 oligosaccharide analogs in which the fluorine atom located at different positions of galactose residue were synthesized in a convergent way for probing carbohydrate-enzyme interaction and carbohydrate-selectin interaction.…”
Section: Oligosaccharide Derivativesmentioning
confidence: 99%
“…Fucosyltransferases and sialyltransferases may compete for the same acceptor substrates, which was demonstrated with N-acetyllactosamine (LacNAc) derivatives 120 . As a result, selective inhibition of sialic acid addition by adding a fluorinated sialic acid analog increases fucosylation 112 .…”
Section: Fucosylationmentioning
confidence: 99%